Sensitivity enhancement of nonlinear micromechanical sensors using parametric symmetry breaking - Xu, Yutao; Yang, Qiqi; Song, Jiahao; Wei, Xueyong (Microsystems & nanoengineering, 2024)
The working mechanism of resonant sensors is based on tracking the frequency shift in the linear vibration range. Contrary to the conventional paradigm, in this paper, we show that by tracking the dramatic frequency shift of the saddle-node bifurcation on the nonlinear parametric isolated branches in response to external forces, we can dramatically boost the sensitivity of MEMS force sensors. Specifically, we first theoretically and experimentally investigate the double hysteresis phenomena of a parametrically driven micromechanical resonator under the interaction of intrinsic nonlinearities and direct external drive. We demonstrate that the double hysteresis is caused by symmetry breaking in the phase states. The frequency response undergoes an additional amplitude jump from the symmetry-breaking-induced parametric isolated branch to the main branch, resulting in double hysteresis in the frequency domain. We further demonstrate that significant force sensitivity enhancement can be achieved by monitoring the dramatic frequency shift of the saddle-node bifurcations on the parametric isolated branches before the bifurcations annihilate. Based on the sensitivity enhancement effect, we propose a new sensing scheme which employs the frequency of the top saddle-node bifurcation in the parametric isolated branches as an output metric to quantify external forces. The concept is verified on a resonant MEMS charge sensor. A sensitivity of up to 39.5 ppm/ f C is achieved, significantly surpassing the state-of-the-art resonant charge sensors. This work provides a new mechanism for developing force sensors of high sensitivity.